Guanxi Economics: Confucius Meets Lenin, Keynes, and Schumpeter in Contemporary China - Manfred Nitsch; Frank Diebel (Intervention. European Journal of Economics and Economic Policies, 2008)
The micro-foundations of the Chinese growth model are analysed within a comprehensive monetary theory of economic development, based on Schumpeter, Keynes, and the contemporary monetary Keynesians. The Confucian traditions and the Leninist party power structure are identified as the main specific traits of the social formation in contemporary China. In the capitalist mode of production, money sets the stage, and the interplay between private creditors and debtors is bundled into a coherent, dynamic whole by the central bank in the economic sphere and by more or less democratic institutions in the political arena. Combining the reproductive, care-taking traits of socialism with the entrepreneurial dynamism of private property and, above all, with the design and enforcement of overall social and economic coherence through the "vanguard" Communist Party makes an unique and ingenious institutional Chinese set-up. The constitutive character of Gu-nxi - the magic word for trust, confidence, reliability, righteousness, mutual benefit and cosmic order - for the working of the whole Chinese economic system is identified and described.
Keywords: D01; E12; O16; P26; 330; China; Chinese Communist Party; economic growth; transitional economy; mode of production